The Role of Lesson Study in Enhancing Faculty Collaboration: A Case Study in Higher Education Institutions: Peran Lesson Study dalam Meningkatkan Kolaborasi Dosen: Studi Kasus di Perguruan Tinggi - Hermawan, Candra; Mahfud; Dian Arief Pradana (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2020)
This study aims to analyze the role of lesson study in enhancing collaboration among faculty members in a higher education setting, specifically within the Study Program at the Faculty of Teacher Training and Education (FKIP). A qualitative research method was employed, using in-depth interviews with five faculty members involved in lesson study activities. The findings indicate that lesson study provides a positive experience for faculty in sharing teaching ideas and practices, as well as increasing their engagement and motivation. Despite challenges such as time constraints and differing viewpoints, faculty reported significant changes in their teaching practices, such as improved responsiveness to student feedback and greater willingness to experiment with new methods. The study concludes that lesson study is an effective strategy for strengthening faculty collaboration and enhancing the quality of learning. Further support from the institution and additional training for faculty are needed to address existing challenges. Limitations of the study include the small sample size and specific context, which may limit the generalizability of the findings across all study programs.